Exploring the Importance of ZBP1 in Sepsis: A Mini Review on It’s Mechanisms and Progress - Liu J; Feng J; Hu J; Chen J; Li FX; Lin N (Journal of Inflammation Research)
Jie Liu,1,2,* Jian Feng,3,* Jian Hu,3 Juan Chen,3 Fu-Xiang Li,2,3 Ning Lin1,2 1Department of Clinical Nutrition, The General Hospital of Western Theater Command, Chengdu, Sichuan, 610083, People’s Republic of China; 2College of Medicine Southwest Jiaotong University, Chengdu, Sichuan, 610031, People’s Republic of China; 3Department of Critical Care Medicine, The General Hospital of Western Theater Command, Chengdu, Sichuan, 610083, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ning Lin, Department of Clinical Nutrition, The General Hospital of Western Theater Command, 270 Tianhui Road, Chengdu, Sichuan, 610083, People’s Republic of China, Tel+86-28-86570983, Email helenmedic@yeah.net Fu-Xiang Li, Department of Critical Care Medicine, The General Hospital of Western Theater Command, Chengdu, Sichuan, 610083, People’s Republic of China, Email lfx98@163.comAbstract: Sepsis is defined as a severe systemic inflammation, often triggered by an infection, resulting in organ dysfunction and mortality. In recent years, ZBP1 (Z-DNA binding protein 1) has garnered significant attention as a critical immune regulatory factor in the pathogenesis of sepsis. This article aims to comprehensively explore the mechanisms by which ZBP1 operates in sepsis and summarize the relevant research progress. This study will seek to highlight the potential of ZBP1 as a therapeutic target and biomarker in the context of sepsis through an in-depth analysis of its functions in cellular signaling, inflammatory response, and immune response. This review seeks to provide new insights for the clinical management of sepsis.Keywords: ZBP1, sepsis, immune regulation, inflammatory response, research progress